Students' boredom in English language classes: Voices from Saudi Arabia - Ali El Deen, Abdul Aziz Mohamed Mohamed (Frontiers in Psychology, 2023)
Although academic research in English-as-a-foreign-language (EFL) emotion has recently increased, there is a paucity of studies related to boredom in the Saudi context. To address this issue, the present study aimed to identify the causes of students' boredom in English classes in the Saudi context and the fluctuations of boredom experiences while studying language skill courses. Utilizing a mixed-methods design, the study drew upon a questionnaire and semi-structured interviews. The questionnaire was completed by 356 from different EFL programs in Saudi universities, whereas the interviews were conducted with 20 students. The results provided a detailed account of the causes of boredom in the Saudi EFL environment. Specifically, the exploratory factor analysis revealed the following seven factors which account for boredom: demotivation, low language learning ability, type of skills-based courses and over-challenging tasks, unfamiliar instructional techniques, teacher feedback areas, under-challenging tasks, and classroom mode, permanent correction, and redundancy. The study also highlighted boredom fluctuations among courses based on language skills via the use of descriptive statistics (means, standard deviations and percentages). Compared to the other courses/lessons, the students were found to have the highest boredom levels in grammar and writing. The paper ends with discussing the implications of the results, and providing suggestions for future research.